Optimalisasi Peran Pelayanan Kesehatan Peduli Remaja (PKPR) dalam Upaya Pencegahan Perilaku Berisiko Pada Remaja di DKI Jakarta - Azzahra, Ariani Shinta; Oktania, Diara; Handayani, Nani; Evrilianto, Andang; Muthmainnah, Susanna; Ilma, Robbiyani; Masyitoh, Masyitoh (Jurnal Ners, 2025)
Adolescents are vulnerable to various risky behaviors, including violence. Although the Adolescent Health Care Program (PKPR) has been developed since 2003 and implemented in 44 community health centers in DKI Jakarta, this study aims to analyze the implementation of PKPR amid the surge in cases of adolescent violence to formulate efforts to optimize its role. To analyze the implementation and identify the challenges of PKPR in DKI Jakarta, as well as to formulate strategies to optimize the role of PKPR in reducing the surge in cases of violence and other risky behaviors among adolescents. This study uses a sequential exploratory mixed-methods study design, located at the DKI Jakarta Community Health Center. The data sources for this study come from primary data (structured questionnaires) and secondary data from official documents from the Health Office. A significant spike in the total number of violence cases was found in DKI Jakarta in 2024 (2084 cases), an increase of 215.8% from 2023. Victims aged 13-17 years were the highest group (552 victims), with boyfriends/girlfriends/friends experiencing a 312.7% spike (326 cases). This reinforces that PKPR has not been able to overcome classic implementation problems related to funding, facilities, and personnel. It is necessary to optimize the role of PKPR to overcome classic implementation problems and adapt to the handling of psychosocial violence cases. Key recommendations include improving health personnel training, providing facilities that ensure privacy and comfort for adolescents, and strengthening networks with schools and youth organizations.